2020
DOI: 10.1186/s12871-020-01208-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic efficacy between rectus sheath blockade, intrathecal morphine with bupivacaine, and intravenous patient-controlled analgesia in patients undergoing robot-assisted laparoscopic prostatectomy: a prospective, observational clinical study

Abstract: Background We explored the analgesic outcomes on postoperative day (POD) 1 in patients undergoing robot-assisted laparoscopic prostatectomy (RALP) who received intravenous patient-controlled analgesia (IV-PCA), rectus sheath bupivacaine block (RSB), or intrathecal morphine with bupivacaine block (ITMB). Methods This was a prospective, observational clinical trial. Patients were divided into three groups: IV-PCA (n = 30), RSB (n = 30), and ITMB (n =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Numerous RCTs showed that multimodal concepts reduce the need for systemic analgesia after ORP or RARP (Andrieu et al, 2009; Brown et al, 2004; Ripolles et al, 2015; Shim et al, 2020; Wu et al, 2005). However, the literature is scarce investigating their impact on quality of recovery as measured by the QoR‐15 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous RCTs showed that multimodal concepts reduce the need for systemic analgesia after ORP or RARP (Andrieu et al, 2009; Brown et al, 2004; Ripolles et al, 2015; Shim et al, 2020; Wu et al, 2005). However, the literature is scarce investigating their impact on quality of recovery as measured by the QoR‐15 questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article “Comparison of analgesic efficacy between rectus sheath blockade, intrathecal morphine with bupivacaine, and intravenous patient-controlled analgesia in patients undergoing robot-assisted laparoscopic prostatectomy: a prospective, observational clinical study” by Shim et al [ 1 ] Yet we think that there are relevant methodological issues and therefore we raise concerns about the potential for generalization of the results for other centers.…”
mentioning
confidence: 99%
“…We appreciate the valuable comments on our submitted article [ 1 ] provided by Löffel et al We compared the analgesic outcomes on postoperative day (POD) 1 in patients undergoing robot-assisted laparoscopic prostatectomy (RALP) who received a rectus sheath block (RSB) or an intrathecal morphine and bupivacaine block (ITMB) with those of patients who received intravenous patient-controlled analgesia (IV-PCA) alone. Below are our responses to each comment.…”
mentioning
confidence: 99%
“…The patients undergoing prostate surgery in our study, including RALP, were elderly (median [IQR] age = 65 [62–71] years) [ 1 ]. Surgeons and physicians typically have clinical concerns regarding postoperative desaturation due to atelectasis or residual effects of analgesic or anesthetic drugs, outside of our trial.…”
mentioning
confidence: 99%
See 1 more Smart Citation